Geographic variation in the use of lymphadenectomy and external‐beam radiotherapy for endometrial cancer: a cross‐sectional analysis of population‐based data. (7th October 2019) - White, B; Nordin, A; Fry, A; Ahmad, A; McPhail, S; Roe, C; Rous, B; Smittenaar, R; Shelton, J
Abstract : Objective: To quantify geographic variation in the use of lymphadenectomy and/or external‐beam radiotherapy (EBRT) for endometrial cancer in England. Design: Cross‐sectional analysis of population‐based data. Setting: English cancer registry data, linked to chemotherapy, radiotherapy and hospital episodes statistics data. Population: Twenty‐two thousand four hundred and eighty‐three women with endometrial cancer presenting without clinical or radiological evidence of distant metastatic spread, diagnosed in England from 2013 to 2016. Methods: Proportions of patients receiving lymphadenectomy and/or EBRT were compared across 19 Cancer Alliances, to identify variations in clinical practice. Two separate logistic regression models assessed the impact on variation of adjustment for tumour and patient characteristics. Main outcome measures: Receipt of lymphadenectomy, receipt of EBRT. Results: There was substantial variation by Cancer Alliance in the adjusted proportion of women with endometrial cancer receiving lymphadenectomy (range 5% [95% CI 4–6%] to 48% [95% CI 45–52%]) and EBRT (range 10% [95% CI 7–12%] to 31% [95% CI 28–33%]), after adjusting for variation in pathological grade, age, comorbidities, deprivation, ethnic group and (EBRT only) FIGO stage. Different approaches to clinical practice were identified; (i) one Cancer Alliance had significantly higher than average lymphadenectomy and significantly lower than average EBRT use, (ii) three had high use of both lymphadenectomy and EBRT, (iii) one had low lymphadenectomy use and high EBRT use, and (iv) three had low use of both lymphadenectomy and EBRT. Conclusions: Lymphadenectomy is probably used to triage for EBRT when lymphadenectomy use is high and EBRT use is low. This is probably a result of variation in local endometrial cancer management guidelines, suggesting that UK recommendations should be clarified. Tweetable abstract: There is geographic variation in England in the use of lymphadenectomy and radiotherapy to treat endometrial cancer. Tweetable abstract: There is geographic variation in England in the use of lymphadenectomy and radiotherapy to treat endometrial cancer.